IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA DI KABUPATEN ASAHAN - MARGARETTA, KAMELIA ERNAWATI; MANALU, DIMPOS; PANJAITAN, FERRY (JURNAL ILMIAH KOHESI, 2022)
This study aims to determine the implementation of the Program Policy for the Empowerment and Family Welfare Program (PKK) in Asahan District and the inhibiting and supporting factors in implementing the policy. This study uses a qualitative descriptive approach using interviews, observation, documentation and data analysis and makes interpretations leading to conclusions. The results of the study indicate that the implementation of the PKK program policy in Asahan Regency in empowering the community and improving the welfare of the family as a whole has been carried out well and provides benefits for the community but is not yet maximized, this can be shown from the lack of Human Resources from PKK administrators, especially in villages and villages, the dasawisma group in the use of technology, the lack of socialization in providing information about the programs organized by the Family Welfare and Empowerment Team for the community, the change in village heads also has an impact on the activities of the Family Empowerment and Welfare Mobilizing Team in the village because there are generally temporary vacancies in management and the lack of skills so that people do not understand the things explained by PKK members, in order to maximize the activities of this program, it is hoped that there will be a policy from the Government so that programs can be implemented. the PKK program continues to run continuously at every change of village head so that the PKK management is not replaced, there is a policy in increasing PKK human resources, especially in inputting dasawisma data into the SIM-PKK application, as well as policies from the village government to professionally educate extension workers who specifically help administrative tasks carried out by the PKK in the villages